2010
DOI: 10.1007/s12028-010-9338-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage Following Neuroendovascular Procedures with Abciximab is Associated with High Mortality: A Multicenter Series

Abstract: Adjunctive use of abciximab to prevent or treat ischemic sequelae during neuroendovascular procedures is associated with a high risk of ICH (18%). We report 9 cases of ICH associated with abciximab administration during neuroendovascular procedures with 44% mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…However, several studies reported that abciximab and eptifibatide may induce fatal intracerebral hemorrhage. 7,[14][15][16] Moreover, abciximab binds irreversibly to the glycoprotein IIb/IIIa receptor causing platelet-function suppression for almost 48 hours after interruption of the infusion. 17 Tirofiban acts as a reversible antagonist of fibrinogen by binding to the glycoprotein IIb/IIIa receptor on platelets.…”
Section: -12mentioning
confidence: 99%
“…However, several studies reported that abciximab and eptifibatide may induce fatal intracerebral hemorrhage. 7,[14][15][16] Moreover, abciximab binds irreversibly to the glycoprotein IIb/IIIa receptor causing platelet-function suppression for almost 48 hours after interruption of the infusion. 17 Tirofiban acts as a reversible antagonist of fibrinogen by binding to the glycoprotein IIb/IIIa receptor on platelets.…”
Section: -12mentioning
confidence: 99%
“…42 Additionally, a recent multicenter series including 12 AIS patients undergoing IAT with adjunctive IV or IA abciximab resulted in sICH in 3 (25%). 43 The use of GP IIb/ IIIa inhibitors in AIS patients undergoing IAT remains investigational and of uncertain benefit.…”
Section: Antithrombotic Agents For Recanalizationmentioning
confidence: 99%
“…However other researchers have identified that intra-arterial abciximab could induce fatal hemorrhage (11,16). In addition, operations such as decompressive craniectomy or external ventricular drainage are sometimes necessary after coil embolization, especially in cases of ruptured cerebral aneurysms.…”
Section: Resultsmentioning
confidence: 99%